Depression and anxiety - inseparable companions of a student? - prevalence of mental disorders in the academic environment, factors predisposing to their occurrence, treatment, forms of assistance - Robert Dubel; Julia Dubel; Kinga Ruszel; Aleksandra Czekaj; Natalia Namroży (Nicolaus Copernicus University in Toruń, 2022)
The studies have a bad reputation for being a demanding and difficult experience for a young person. Studies are a time that presents young adults with many challenges and induces the necessity of numerous sacrifices, as well as provides a huge dose of everyday stress. Taking into account the current pace of life, to which man as a species is not evolutionarily adapted, juxtaposed with everyday extreme stressors, the question arises - what are the consequences and costs of a young man in response to such a lifestyle. What mental health problems can arise from experiencing long-term stress? The aim of this work is to summarize and collect available information on the prevalence, factors predisposing to the occurrence and forms of help and treatment of depression, and to list the most popular mental disorders in the group of students.